Synchrotron Infrared Spectroscopy of Microporous Materials - Howe, Russell F. (Makara Journal of Science, 2016)
This review describes the ways in which synchrotron infrared radiation can be used to perform infrared spectroscopy on catalyst materials. The enhanced brightness of the synchrotron source over a conventional laboratory source allows for microspectroscopy to be performed on single crystals of microporous materials down to 10 microns in size. A second application was performed in the far-infrared region, which is generally difficult using laboratory instruments. The review presents typical results from both areas and discusses future prospects.